The Effect Of Social Media Marketing On Product Purchasing Decisions At Lunalice Boutique Bengkulu City - Sahputra, Muhammad Redo; Anggriani, Ida; Rahman, Abdul (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
In terms of using social media marketing that attracts consumers and potential consumers, it is necessary to pay attention to the advantages of products that allow consumers to attract consumers to make purchases, besides that the content created on the business actor's social media platform must also be packaged attractively and provide detailed information about the products being marketed so that this will attract consumers to purchase products when they see advertisements distributed on the business actor's social media.The purpose of this study was to determine whether Social Media Marketing has an effect on product purchasing decisions at Lunalice Boutique, Bengkulu City. In this study, the data were analyzed using statistical methods. Data processing in this study used a statistical program in the form of SPSS. The statistical test used to analyze the data in this study uses simple linear regression analysis. The results of the discussion show that social media marketing has an effect on purchasing decisions at Lunalice Boutique, Bengkulu City.